226k views
3 votes
Please a need the answer and the solution please

Please a need the answer and the solution please-example-1
User Taunya
by
5.8k points

1 Answer

4 votes

Answer:

Explanation:

To find the first table y = 4x + 2, to find each y value we have to substitute each x value into the equation.

4(-2) + 2 = -6 so -2 is going to have the y as -6

4(-1) + 2 = -2 so -1 is going to have the y as -2

4(0) + 2 = 2 so 0 is going to have the y as 2

4(1) + 2 = 6 so 1 is going to have the y as 6

4(2) + 2 = 10 so 2 is going to have the y as 10

So these are the points you would graph (-2, -6), (-1, -2), (0, 2), (1,6), and (2, 10)

For the next talbe y = 3x + 1 we do the same thing

3(-2) + 1 = -5 so -2 is going to have the y as -5

3(-1) + 1 = -2 so -1 is going to have the y as -2

3(0) + 1 = 1 so 0 is going to have the y as 1

3(1) + 1 = 4 so 1 is going to have the y as 4

3(2) + 1 = 7 so 2 is going to have the y as 7

The ooints to graph are (-2, -5), (-1, -2),(0,1), (1, 4) and (2,7)

For the next table y = 6x - 5

6(-2) - 5 = -17 so -2 is going to have the y as -17

6(-1) - 5 = -11 so -1 is going to have the y as -11

6(0) - 5 = -5 so 0 is going to have the y as -5

6(1) - 5 = 1 so 1 is going to have the y as 1

6(2) - 5 = 7 so 2 is going to have the y as 7

The points to graph (-2, -17), (-1, -11), (0, -5), (1, 1) and (2, 7)

For the next table y = 5 + 2x

5 + 2(-4) = -3 so -4 is going to have the y as -3

5 + 2(-2) = 1 so -2 is going to have the y as 1

5 + 2(0) = 5 so 0 is going to have the y as 5

5 + 2(3) = 11 so 3 is going to have the y as 11

5 + 2(5) = 15 so 5 is going to have the y as 15

(-4, -3), (-2, 1), (0, 5), (3, 11) and (5, 15)

For the next table y = 8x - 10

8(-4) - 10 = -42 so -4 is going to have the y as -42

8(-2) - 10 = -26 so -2 is going to have the y as -26

8(0) - 10 = -10 so 0 is going to have the y as -10

8(2) - 10 = 6 so 2 is going to have the y as 6

8(4) - 10 = 22 so 4 is going to have the y as 22

(-4, -42), (-2, -26), (0, -10), (2, 6) and (4, 22)

For the last table

2(-2) = -4 so -2 is going to have the y as -4

2(-1) = -2 so -1 is going to have the y as -2

2(0) = 0 so 0 is going to have the y as 0

2(-1) = -2 so -1 is going to have the y as -2

2(-2) = -4 so -2 is going to have the y as -4

(-2, -4), (-1, -2), (0, 0), (-1, -2) and (-2, -4)

User Dbaer
by
6.1k points